Answer:
[tex]f(0.5) = 42.55[/tex]
Step-by-step explanation:
Given
[tex]f(-5) = 26[/tex]
[tex]f(3) = 54[/tex]
Required
Find f(0.5)
An exponential function is of the form:
[tex]y=ab^x[/tex]
For: [tex]f(-5) = 26[/tex]
[tex]x = -5[/tex] [tex]y = 26[/tex]
So, we have:
[tex]26 = ab^{-5}[/tex] --- (1)
For [tex]f(3) = 54[/tex]
[tex]x = 3[/tex] [tex]y =54[/tex]
So, we have:
[tex]54 = ab^3[/tex] --- (2)
Divide (2) by (1)
[tex]\frac{54}{26} = \frac{ab^3}{ab^{-5}}[/tex]
[tex]\frac{54}{26} = \frac{b^3}{b^{-5}}[/tex]
Apply law of indices
[tex]\frac{54}{26} = b^{3-(-5)}[/tex]
[tex]\frac{54}{26} = b^{3+5}[/tex]
[tex]\frac{54}{26} = b^{8}[/tex]
[tex]2.07692307692= b^{8}[/tex]
Take 8th roots of both sides
[tex]b = \sqrt[8]{2.07692307692}[/tex]
[tex]b = 1.09566440144[/tex]
[tex]b = 1.10[/tex]
Substitute 1.10 for b in [tex]54 = ab^3[/tex]
[tex]54 = a * 1.10^3[/tex]
[tex]54 = a * 1.331[/tex]
Solve for a
[tex]a = \frac{54}{1.331}[/tex]
[tex]a = 40.57[/tex]
To solve for f(0.5), we have:
[tex]y=ab^x[/tex]
[tex]f(0.5) = 40.57 * 1.10 ^ {0.5}[/tex]
[tex]f(0.5) = 40.57 * 1.04880884817[/tex]
[tex]f(0.5) = 42.5501749703[/tex]
[tex]f(0.5) = 42.55[/tex] (approximated)